2013
DOI: 10.1021/ja4033956
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Reactions of Enantiomerically Pure α-Functionalized Grignard Reagents

Abstract: A strategy for the generation of enantiomerically pure α-functionalized chiral Grignard reagents is presented. The approach involves the synthesis of α-alkoxy and α-amino sulfoxides in ≥99:1 dr and ≥99:1 er via asymmetric deprotonation (s-BuLi/chiral diamine) and trapping with Andersen's sulfinate (menthol derived). Subsequent sulfoxide → Mg exchange (room temperature, 1 min) and electrophilic trapping delivers a range of enantiomerically pure α-alkoxy and α-amino substituted products. Using this approach, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Regrettably, the yield of chain extension was low throughout (TBSOTf boosted yield by only 3–5 %); however, in all cases the StReCH adducts isolated following oxidative work‐up ( 21–25 ) were single diastereoisomers and where determined, their ee matched that of the sulfinyl epoxide employed. Stereochemically distinct 2°/2° vicinal diols (and related monosilylated adducts) were generated from epimeric sulfinyl epoxides, and it was verified by comparison to literature data for known compounds ( 21s , 22a / s , 24a , and 25a / s )13,17 that, as anticipated, cis ‐epoxides led to anti products while the trans ‐isomers gave instead the corresponding syn adducts. Monosubstituted sulfinyl epoxides 12 bearing simple alkyl groups in the β‐position (R 1 = H, R 2 /R 3 = H/Me or H/ n Pr, cis ‐ and trans ‐isomers) were likewise examined and gave similar results to those illustrated (i.e., yields 10–16 % from 1 , R 0 = CH 2 Bn).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Regrettably, the yield of chain extension was low throughout (TBSOTf boosted yield by only 3–5 %); however, in all cases the StReCH adducts isolated following oxidative work‐up ( 21–25 ) were single diastereoisomers and where determined, their ee matched that of the sulfinyl epoxide employed. Stereochemically distinct 2°/2° vicinal diols (and related monosilylated adducts) were generated from epimeric sulfinyl epoxides, and it was verified by comparison to literature data for known compounds ( 21s , 22a / s , 24a , and 25a / s )13,17 that, as anticipated, cis ‐epoxides led to anti products while the trans ‐isomers gave instead the corresponding syn adducts. Monosubstituted sulfinyl epoxides 12 bearing simple alkyl groups in the β‐position (R 1 = H, R 2 /R 3 = H/Me or H/ n Pr, cis ‐ and trans ‐isomers) were likewise examined and gave similar results to those illustrated (i.e., yields 10–16 % from 1 , R 0 = CH 2 Bn).…”
Section: Resultssupporting
confidence: 59%
“…Significantly, Satoh and co‐workers reported that treatment of sulfinyl epoxides 12 with organolithium compounds at low temperature produces transient lithiated epoxides 5 [Equation (1)] that can be intercepted in good yield with a range of simple electrophiles 11. Given that related sulfoxide–metal exchange phenomena12 have been successfully employed to trigger other types of StReCH reactions,1,3,13 we elected to investigate the chain extension of boronates using carbenoids derived from Satoh's method because of its potential to generate any type of lithiooxirane. Herein, we describe our findings and disclose that sulfoxide–lithium exchange from cis ‐ or trans ‐ mono‐, di‐, and tri‐substituted sulfinyl epoxides in the presence of boronic esters leads to chain‐extended adducts with excellent diastereoselectivity in a majority of examples.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding these issues, sulfoxide–lithium‐exchange‐based StReCH chemistry enjoys an operational simplicity that is unrivalled by alternate direct metallation‐based approaches. The recent discovery by O’Brien and co‐workers that Hoppe‐type metallated carbamates can be efficiently generated from stereodefined α‐carbamoyloxy sulfoxides23a means that the advantages of sulfoxide–metal‐exchange‐based StReCH can now be interfaced with the use of a more robust carbenoid type 9…”
Section: Resultsmentioning
confidence: 99%
“…) make this tactic hardly attractive from a green chemistry perspective, clearly violating the 3rd, 4th, 5th, and 7th Anastas’ Principles . Notwithstanding, the sparteine‐mediated methodology is quite flexible and adaptable to conceptually different chemistries to access highly versatile enantioenriched building blocks (Scheme a), for example, Aggarwal's homologated boronates, O'Brien's chiral sulfoxides, and Baudoin's arenes, which can be further elaborated, for example, in Aggarwal's assembly‐line synthesis …”
Section: Introductionmentioning
confidence: 99%
“…[10] make this tactic hardly attractive from ag reen chemistry perspective, clearly violating the 3rd, 4th, 5th, and7 th Anastas' Principles. [11] Notwithstanding,t he sparteine-mediated methodology is quite flexible and adaptable to conceptually different chemistries to access highly versatile enantioenriched building blocks( Scheme 1a), for example, Aggarwal's homologated boronates, [12] O'Brien's chiral sulfoxides, [13] andB audoin's arenes, [14] which can be further elaborated, for example, in Aggarwal's assembly-line synthesis. [15] During ar ecent studyo nt he synthesis of thioamides from isothiocyanates and organolithium reagents, [16] we noticedt hat the combination of sparteine and the sustainable solvent cyclopentyl methyl ether (CPME) [17] effectively achievedahigh level of stereocontrol (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%